Some bayes estimation startegies in exponential distribution under a weighted loss function - A. Kiapour; mehran naghizadeh qomi (Journal of Hyperstructures, 2018)
In Bayesian approach, prior knowledge is often vague and any elicited prior distribution is only an approximation to the true one. E-Bayes and robust Bayes approaches consider a class of prior distributions instead of a single prior. In this paper, we deal with Bayes, E-Bayes and robust Bayes estimation of the exponential scale-parameter under a weighted loss function. We conduct a simulation study for comparison of these estimators.